Boccia court analysis for promoting elderly physical activity - Calado, Alexandre (2019)
Physical inactivity is one of the leading risk factors for global mortality. Older adults, in particular, are more probable to suffer the consequences of physical inactivity, since it is one of the most sedentary age groups. On the other hand, engaging physical activity can have various benefits for the prevention of several diseases and functional loss prevention, therefore, it is critical to encourage its regular practice amongst the elderly. Boccia is a simple precision ball sport that is easily adaptable for individuals with physical limitations, which makes it a perfectly good game for this circumstance. The present paper proposes a ball-detection based system for monitoring the Boccia court, compute the current game score and display it on a user interface. The future goal of such system will be to motivate the elders to participate more frequently in the Boccia game and make the overall game experience more enjoyable. The proposed system was tested with twenty video recordings of different simulated game situations. Overall, the obtained results were encouraging, having only one incorrect game score being computed by the developed algorithm.